THE USE OF VOCABULARY NOTEBOOKS AND ITS EFFECT ON WORD RETENTION - Watcharee Paisart (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This study explores the impact of vocabulary notebooks on word retention among Thai university students enrolled in an English for Specific Purposes (ESP) course. It aims to: 1. Investigate the effectiveness of vocabulary notebook use and its vocabulary retention; 2. Compare the results of vocabulary notebook use among different groups of language proficiency level; and 3. Study students’ attitudes towards their use of vocabulary notebook to help on word retention. Twenty-four participants were divided into a control group and an experimental group, categorized into three sub-groups based on English proficiency – low, proficient, and high. The research employed a mixed-methods design, utilizing pretest-posttest assessments, questionnaires, and a semi-structured interview. Quantitative data were analyzed using descriptive statistics, including percentages, and frequency counts. Results showed that 60% ( 0.6) of students using notebooks improved posttest scores, compared to 44.44% ( 0.44) of those who did not. High-proficient learners showed the most consistent gains, with all participants improving. Notebook use varied by proficiency in format, color, and content. Qualitative data (analyzed by coding) indicated generally positive attitudes, though some students considered it outdated and preferred digital alternatives. Findings suggest vocabulary notebooks can effectively enhance retention, especially when adapted to learners’ proficiency and preferences, offering pedagogical implications for ESP instruction.